What drives the FOMC's dot plots?. (June 2020) - Gerlach, Stefan; Stuart, Rebecca
Highlights: We fit curves for the FOMC's dot plots and compute constant horizon projections. Labour market variables are important drivers of these projections. Data on financial markets and trade and investment also play important roles. In contrast, inflation rarely matters. Out-of-sample tests suggest our model fits well compared to other specifications. Abstract: The Federal Open Market Committee (FOMC) releases quarterly its members' views about what federal funds rate will be appropriate at the end of the current and the next two or three years, and in the "longer run." We construct constant horizon interest rate projections one, two and three years ahead and use real-time data on 32 important macroeconomic time series to study how these variables impact on the FOMC's interest-rate setting. News regarding the labour market is particularly important at all horizons. At longer horizons, financial market, trade and output news also matter.